Pengaruh Lama Fermentasi Terhadap Karakteristik Fermented Rice Drink Sebagai Minuman Probiotik Dengan Isolat Lactobacillus sp. F213 - Adi Wira Kusuma, Gusti Putu; Ayu Nocianitri, Komang; Kartika Pratiwi, I Desak Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2020)
This research aims to identify the effect of fermentation time on the characteristics of fermented rice drinks and to identify the proper fermentation time to produce fermented rice drink with the best characteristics. Fermentation of fermented rice drink used the Lactobacillus sp. F213 isolates. This research used a randomized block design (RBD) with fermentation time as treatment, namely 18, 20, 22, 24, and 26 hours. Each treatment was repeated 3 times resulting in 15 experimental units. The data were analyzed by analysis of variance (ANOVA) and if the treatment affected the variable, then proceed with the Duncan test. The results showed that the fermentation time had a significant effect on total LAB, total sugar, total acidity, pH, and sour taste score of fermented rice drink. The 22 hours fermentation time treatment produced the best characteristics of fermented rice drink, with the following criteria: total LAB 13,26 Log CFU/ml, total sugar 22, 35 %, total acidity 1,71 %, pH 3,99, the color and taste that sweet and rather sour were preferred, the aroma was rather preferred, and overall acceptance was preferred. Keywords: probiotic, fermented rice drink, Lactobacillus sp. F213.